Comparison of Predictive Ability of Computed Tomography and Magnetic Resonance Imaging in Patients with Carotid Atherosclerosis Complicated with Stroke - Jiangfeng ZHOU; Hongling CHEN; Tao YANG; Cuihong XING; Fengxia JIA (Tehran University of Medical Sciences, 2019)
Background: To investigate the characterizations of CT (computed tomography) and MRI (magnetic resonance imaging) in patients with carotid atherosclerosis. Methods: A retrospective analysis was performed on the medical records of 264 patients with carotid atherosclerosis underwent CT and MRI in Linyi Central Hospital, Linyi, China from January 2010 to January 2016. Among them, 142 patients with ischemic stroke were in experimental group (test group), another 122 patients in control group. The lumen stenosis degree, plaque fibrous cap status, calcification information and vascular plaque hemorrhage in the carotid artery fork of patients detected by CT and MRI were collected. Results: The detection rate of the plaque calcification of patients detected by MRI was lower than that detected by CT in the experimental group (P<0.05). Patients in the experimental group had higher average vascular stenosis degree detected by CT and MRI than those in the control group (P<0.01). The average vascular stenosis degree of patients detected by MRI was higher than that detected by CT in the experimental group (P<0.05). Patients in the experimental group had higher unstable fibrous cap number detected by CT and MRI than those in the control group (P<0.01). Patients in the experimental group had significantly higher number of vascular plaque small focus hemorrhage than those in the control group (P<0.05). Conclusion: Patients with carotid atherosclerotic complicated with stroke have higher plaque calcification number, vascular stenosis degree and unstable fibrous cap number. Both CT and MRI can better predict the risk of stroke.